Empire and Power in the Reign of Suleyman Narrating the Sixteenth-Century Ottoman World - Sahin, Kaya, 1974- (Cambridge University Press, 2013)
"On a torrid August day in 2009, I visited Celalzade Mustafa's final resting place in Istanbul's Eyüp district, in a neighborhood called Nisanca. The chancellor (nisanci) is buried in the cemetery adjoining the small mosque built for him by Sinan, the chief imperial architect. His brother Salih, a teacher, judge and religious scholar, is buried nearby, but the sepulchres of poets who received plots from this patron of poetry have disappeared. The mosque, adorned with glazed tiles, has changed significantly since the mid-sixteenth century. It was damaged in a fire in 1729, and was rebuilt following a more devastating fire in 1780. The mansion where Mustafa composed his works, welcomed fellow literati, and provided advice to young and aspiring secretaries is long gone, probably destroyed in the fire of 1780, if not before".